Development of metal oxide nanostructures incorporated with carbon matrix for electrochemical applications / Numan Arshid - Numan , Arshid (2018)
Over the last few decades, nanomaterials have found prodigious potential in various applications of different research fields. Although the metal oxide frame work is not a new class of nanomaterials yet its potential is not explored extensively, especially for electrochemical applications. One of the most significant research motivations for metal oxide frame works come from their tunable morphology, porosity, rigidity/flexibility, variety and facile design which make them capable of using in variety of advanced energy conversion, energy storage and electrochemical sensing devices. However, unsupported metal oxide nanostructures suffers from particle aggregations which lead to decrease their electrochemical surface area. In this work, one step hydrothermal route was used to develop binary nanocomposite of metal oxide (Co3O4) and carbonaceous matrix such as graphene, multiwall carbon nanotubes (MCNTs). The first system, binary composite of reduced graphene intercalated with cobalt oxide (Co3O4) nanocubes was synthesized and the contents of Co3O4 precursor were optimized with respect to fixed amount of reduced graphene oxide (rGO). The rGO−Co3O4 nanocubes was used for supercapacitor application. It was found that with 0.5 mmol of cobalt precursor (A2) gave the highest specific capacity (125 Cg-1) in three electrode cell system. Same nanocomposite was used to fabricate rGO−Co3O4 nanocubes//activated carbon hybrid supercapacitor and the maximum energy and power density was found to be 7.75 Wh.k-1 and 996.42 W.kg-1, respectively. In second system, composite of rGO−Co3O4 nanograins was optimized by varying the contents of rGO with respect to the fixed concentration of Co3O4 precursor. The performance of rGO−Co3O4 nanograins was evaluated for electrochemical sensing of dopamine. The nanocomposite rGO−Co3O4 (B3) with 9.1 wt. % of rGO was optimized on the basis of oxidation current of dopamine. The B3 modified glassy carbon electrode gave 0.277 μL (S/N=3) limit of detection for dopamine in the linear range of 1−30 μL. The performance of B3 modified GCE was also satisfactory in real time urine sample and in the presence of physiological interfering analytes. In the last system, Co3O4 nanocubes were fabricated with MWCNT and the contents of MWCNT with respect to the fixed amount of cobalt precursor were optimized. The MWCNT−Co3O4 nanocube was used for supercapacitor and electrochemical sensing of dopamine application. In both applications, MWCNT−Co3O4 nanocubes (C4) with 16 wt. % of MWCNT demonstrated excellent electrochemical performance compared to its counterparts. The maximum specific capacity was 142 Cg-1 using three electrode cell system. The highest energy density was found to be 19.28 Wh.kg-1 at power density of 309.85 W.kg-1. The optimized nanocomposite (C4) also showed excellent electrochemical performance for dopamine detection. The limit of detection is found to be 0.176 μL in the linear range of 1−30 μL. However, MWCNT−Co3O4 nanocube showed poor selectivity towards dopamine detection. Overall, MWCNT−Co3O4 nanocubes gave better performance for hybrid supercapacitor compared to rGO−Co3O4 nanocubes in terms of specific capacity and energy density. However, rGO−Co3O4 nanograins endowed good sensing capability for dopamine detection in terms of selectivity compared to MWCNT−Co3O4 nanocubes. This work embark the frontiers of carbonaceous materials for electrochemical applications.